ChemInform Abstract: Subphthalocyanines, Subporphyrazines, and Subporphyrins: Singular Nonplanar Aromatic Systems. Issue 16 (22nd April 2014) - Claessens, Christian G.; Gonzalez‐Rodriguez, David; Rodriguez‐Morgade, M. Salome; Medina, Anais; Torres, Tomas
Abstract Review: synthesis, characterization, properties, and applications, 444 refs.